eROSITA narrowband maps at the energies of soft X-ray emission lines - Zheng, Xueying; Ponti, Gabriele; Locatelli, Nicola; Sanders, Jeremy; Merloni, Andrea; Becker, Werner; Comparat, Johan; Dennerl, Konrad; Freyberg, Michael; Maitra, Chandreyee; Sasaki, Manami; Strong, Andrew; et al. (Astronomy & Astrophysics, 2024)
Hot plasma plays a crucial role in regulating the baryon cycle within the Milky Way, flowing from the energetic sources in the Galactic center and plane, to the corona and the halo. This hot plasma represents an important fraction of the Galactic baryons, plays a key role in galactic outflows and is an important ingredient in galaxy evolution models. Taking advantage of the Spectrum-Roentgen-Gamma (SRG)/eROSITA first all-sky survey (eRASS1), in this work our aim is to provide a panoramic view of the hot circumgalactic medium (CGM) of the Milky Way. Compared to the previous all-sky X-ray survey performed by ROSAT, the improved energy resolution of eROSITA enabled us to map, for the first time, the sky within the narrow energy bands characteristic of soft X-ray emission lines. These lines provide essential information on the physical properties of the hot plasma. Here we present the eROSITA eRASS1 half sky maps in narrow energy bands corresponding to the most prominent soft X-ray lines, O vii and O viii, which allowed us to constrain the distribution of the hot plasma within and surrounding the Milky Way. We corrected the maps by removing the expected contribution associated with the cosmic X-ray background, the time-variable solar wind charge exchange, and the local hot bubble. We applied corrections to mitigate the effect of absorption, therefore highlighting the emission from the CGM of the Milky Way. We used the line ratio of the oxygen lines as a proxy to constrain the temperature of the warm-hot CGM, and we defined a pseudo-temperature T map. The map highlights how different regions are dominated by different thermal components. Toward the outer halo, the temperature distribution of the CGM on angular scales of 2-20 deg is consistent with being constant ΔT/〈T〉 ≤ 4%, with a marginal detection of ΔT/〈T〉 = 2.7% ± 0.2% (statistical) ±0.6% (systematic) in the southern hemisphere. Instead, significant variations of ∼12% are observed on scales of many tens of degrees when comparing the northern and southern hemispheres. The pseudo-temperature map shows significant variations across the borders of the eROSITA bubbles, suggesting temperature variations, possibly linked to shocks, between the interior of the Galactic outflow and the unperturbed CGM. In particular, a shell characterized by a lower line ratio appears close to the edge of the eROSITA bubbles.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Galaxy: general; Galaxy: structure; X-rays: diffuse background; X-rays: general